Polyimide film and method for producing same

By storing and controlling the thermal expansion coefficient of the polyimide film under humidity conditions, the problem of the decrease in dimensional stability of the polyimide film after humidity changes is solved, and the effect of dimensional consistency in the high-temperature manufacturing process is achieved, and the quality of the flexible metal film circuit board is improved.

JP2025510932AActive Publication Date: 2025-04-15PI ADVANCED MATERIALS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024557250
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-30
Filing Date
2023-03-28
Publication Date
2025-04-15
Estimated Expiration
2043-03-28

AI Technical Summary

Technical Problem

In the prior art, polyimide films have a reduced dimensional stability after being exposed to a changing humidity environment, especially when manufacturing flexible metal film circuit boards at high temperatures, the dimensional change affects product quality.

Method used

By storing at 50%RH for 48 hours, the thermal expansion coefficient of temperatures from 25°C to 400°C was measured using a thermodynamic analyzer (TMA), ensuring that the temperature-raising thermal expansion coefficient in the TD direction was in the range of -1.5ppm/°C to 6ppm/°C. Meanwhile, a provided manufacturing method is employed, including coating a polyamic acid solution on the support and forming a polyimide film by heating and stretching.

Benefits of technology

The polyimide film maintains good dimensional stability after humidity exposure and maintains dimensional consistency during the manufacturing process of metal film circuit boards, thereby improving product quality and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025510932000001_ABST
    Figure 2025510932000001_ABST
Patent Text Reader

Abstract

The present invention provides a polyimide film and a method for producing the same, in which, in measurement of dimensional change using a thermomechanical analyzer (TMA) after storage for 48 hours under a humidity condition of 50% RH and then undergoing a temperature rise process from 25°C to 400°C, the temperature rise thermal expansion coefficient in the TD direction (50 to 200°C) is -1.5 ppm / °C or more and 6 ppm / °C or less, the temperature rise thermal expansion coefficient (50 to 200°C) is the slope of a line connecting a dimensional measurement value in the TD direction of the polyimide film measured at 200°C in a first run during the temperature rise process and a dimensional measurement value in the TD direction of the polyimide film measured at 50°C in a first run during the temperature rise process, and the dimensional measurement value in the TD direction corresponds to a dimensional change value calculated by converting the length of the polyimide film sample used in the measurement using the thermomechanical analyzer to 1 m.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyimide film having excellent dimensional stability even after exposure to humidity for a certain period of time, and a method for producing the same. [Background technology]

[0002] Polyimide (PI) is a polymeric material based on imide rings, which have excellent chemical stability along with a rigid aromatic main chain, and has the highest levels of heat resistance, chemical resistance, electrical insulation, chemical resistance, and weather resistance among organic materials.

[0003] Polyimide films have been attracting attention as a material for a variety of electronic devices that require the above-mentioned properties.

[0004] An example of a microelectronic component to which polyimide films are applied is a flexible thin circuit board having a high degree of circuit integration so as to accommodate the trend toward lighter and smaller electronic products. Polyimide films are particularly widely used as insulating films for thin circuit boards.

[0005] The thin circuit board generally has a structure in which a circuit including metal foil is formed on an insulating film. Such a thin circuit board is broadly called a flexible metal foil clad laminate, and when a thin copper plate is used as the metal foil, it is more narrowly called a flexible copper foil laminate. It is also called Copper Clad Laminate (FCCL).

[0006] Examples of methods for producing flexible metal foil laminates include (i) a casting method in which polyamic acid, a precursor of polyimide, is cast or coated onto a metal foil and then imidized, (ii) a metallizing method in which a metal layer is directly formed on a polyimide film by sputtering, and (iii) a lamination method in which a polyimide film and a metal foil are bonded together by heat and pressure via a thermoplastic polyimide. In particular, the metallizing method is a method for producing flexible metal foil laminates by sputtering a metal such as copper on a polyimide film having a thickness of, for example, 20 to 38 μm, and sequentially depositing a tie layer and a seed layer. This method is advantageous in forming ultra-fine circuits with a circuit pattern pitch of 35 μm or less, and is widely used to manufacture flexible metal foil laminates for COF (chip on film).

[0007] In fact, polyimide films used in the manufacture of flexible metal foil laminates go through various stages before manufacture, including transportation and storage, during which they are placed in environments where humidity, temperature, and other factors change. In particular, there is a problem that the dimensional stability of the polyimide film is reduced during exposure to humidity during transportation, storage, etc., and during application of high temperatures during the manufacturing process of the flexible metal foil laminate. Therefore, there is a strong demand for polyimide films that maintain their dimensional stability even after being exposed to certain environments (especially humidity) during transportation, storage, and the like.

[0008] The matters described in the above background art are intended to aid in understanding the background of the invention, and may include matters that are not prior art already known to those having ordinary skill in the art to which this technology pertains. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Republic of Korea Patent No. 10-1258432 Summary of the Invention [Problem to be solved by the invention]

[0010] Therefore, an object of the present invention is to provide a polyimide film that has excellent dimensional stability even after being exposed to humidity for a certain period of time. However, the problems to be solved by the present invention are not limited to those mentioned above, and other problems not mentioned will be clearly understood by those skilled in the art from the following description. [Means for solving the problem]

[0011] In order to achieve the above object, one aspect of the present invention is to provide a method for producing a 50% RH ... When measuring the dimensional change using a thermomechanical analyzer (TMA) during the heating process from 25°C to 400°C, the thermal expansion coefficient in the traverse direction (TD) (50~200°C) is -1.5ppm / °C or more and 6ppm / °C or less. The temperature-rise thermal expansion coefficient (50 to 200°C) is a slope of a line connecting a measured dimension of the polyimide film in the TD direction measured at 200°C in the first run during the temperature-rise process and a measured dimension of the polyimide film in the TD direction measured at 50°C in the first run during the temperature-rise process, The measured dimension in the TD direction corresponds to a dimensional change calculated by converting the length of the polyimide film sample used in the measurement with the thermomechanical analyzer to 1 m. A polyimide film is provided.

[0012] Another aspect of the present invention provides a method for producing the polyimide film, the method including the steps of: providing a polyamic acid solution obtained from a dianhydride acid component and a diamine component; casting and applying the polyamic acid solution onto a support and heating to produce a self-supporting film of the polyamic acid solution; and imidizing and stretching the self-supporting film to produce a polyimide film.

[0013] Yet another aspect of the present invention provides a flexible metal foil laminate comprising the above polyimide film and an electrically conductive metal foil.

[0014] Yet another aspect of the present invention provides an electronic component comprising the flexible metal foil laminate described above. Effect of the Invention

[0015] The present invention provides a polyimide film that has excellent dimensional stability even after exposure to humidity for a certain period of time, and therefore provides a polyimide film that has excellent dimensional stability even during the lamination process of metal foil. Such polyimide films are applicable to various fields requiring polyimide films with excellent dimensional stability, for example, flexible metal foil laminates produced by a metallizing method or electronic parts including such flexible metal foil laminates. [Brief description of the drawings]

[0016] [Figure 1] 1 is a graph showing the results of dimensional change measurement using a thermomechanical analyzer (TMA) for polyimide films of Examples 1 and 4 of the present application undergoing a temperature increase process from 25° C. to 400° C. [Diagram 2] 1 is a graph showing the results of dimensional change measurement using a thermomechanical analyzer (TMA) for polyimide films of Comparative Examples 1 and 4 of the present application undergoing a temperature increase process from 25° C. to 400° C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept that corresponds to the technical idea of ​​the present invention, based on the principle that an inventor can appropriately define the concept of a term in order to explain his / her invention in the best possible way.

[0018] Therefore, it should be understood that the configuration of the embodiment described in this specification is merely one of the most preferred embodiments of the present invention and does not fully represent the technical ideas of the present invention, and that there may be various equivalents and modifications that can replace them at the time of this application.

[0019] In this specification, the singular expression includes the plural expression unless the context clearly indicates otherwise. It should be understood that in this specification, the terms "comprise", "comprise", "have" and the like are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, and do not preclude the possibility of the presence or addition of one or more other features, numbers, steps, components, or combinations thereof.

[0020] As used herein, "dianhydride acid" is intended to include precursors or derivatives thereof which may not technically be dianhydrides but which nevertheless must react with a diamine to form a polyamic acid which is then converted back to a polyimide.

[0021] As used herein, "diamine" is intended to include precursors or derivatives thereof, which may not technically be diamines, but which nevertheless must react with a dianhydride to form a polyamic acid, which is then converted back to a polyimide.

[0022] Whenever an amount, concentration, or other value or parameter is given herein as a range, a preferred range or a list of an upper preferred value and a lower preferred value, it should be understood to specifically disclose all ranges formed by any pair of any upper range limit or preferred value, and any lower range limit or preferred value, regardless of whether a range is otherwise disclosed.

[0023] Where a range of numerical values ​​is recited herein, unless otherwise stated, the range is intended to include the endpoints thereof, and all integers and fractions within the range. It is not intended that the scope of the invention be limited to the specific values ​​recited when defining a range.

[0024] In one embodiment of the present invention, a polyimide film has a temperature rise coefficient of thermal expansion (50 to 200°C) of -1.5 ppm / °C or more and 6 ppm / °C or less, when a dimensional change is measured by a thermomechanical analyzer (TMA) while the polyimide film is heated from 25°C to 400°C. The temperature rise coefficient of thermal expansion (50 to 200°C) may be a slope of a line connecting a measured dimension of the polyimide film in the TD direction measured at 200°C in a first run during the temperature rise process and a measured dimension of the polyimide film in the TD direction measured at 50°C in a first run during the temperature rise process.

[0025] In addition, the dimension measurement value in the TD direction may correspond to a dimensional change value calculated by converting the length of the polyimide film sample used in the measurement by the thermomechanical analyzer to 1 m. That is, the polyimide film of the present invention is a polyimide film having a first run during the temperature rise process. The slope of a line connecting the measured dimension in the TD direction of the polyimide film measured at 200°C in the first run and the measured dimension in the TD direction of the polyimide film measured at 50°C in the first run during the heating process is -1.5 ppm / °C or more.

[0026] Polyimide film expands in the MD (machine direction, lengthwise direction) and TD (traverse direction, width direction) during the temperature rise process, but in actual FCCL manufacturing, the pattern progresses in the MD direction, and the PI film and Cu layer form a repeated pattern in the TD direction. Therefore, the expansion and contraction in the TD direction are particularly important factors that determine the quality of FCCL.

[0027] The slope of the straight line of the polyimide film of the present invention may be preferably 5.5 ppm / ° C. or less, and more preferably 5.0 ppm / ° C. or less. Polyimide films with a slope of the line between -1.5 ppm / °C and 6 ppm / °C had excellent dimensional stability even after exposure to humidity for a certain period of time, and the dimensional stability of the polyimide film was maintained even after lamination of metal foil by coating, sputtering and / or vapor deposition. Polyimide films with a slope of less than -1.5 ppm / °C or more than 6 ppm / °C exhibited reduced dimensional stability after exposure to humidity for a certain period of time, and the quality of flexible metal foil laminates laminated with metal foil by coating, sputtering and / or vapor deposition was significantly reduced.

[0028] Here, the measurement of the dimensional change by the thermomechanical analyzer (TMA) was carried out under the following conditions. Measurement mode: tension mode, load 5g, Sample length: 16 mm (width direction length), Sample width: 4mm, Heating start temperature: 25℃, End temperature: 400℃ (no maintenance time at 400℃)

[0029] The polyimide film of the present invention may have a coefficient of thermal expansion (CTE) in the TD direction of 1 ppm / °C or more and 10 ppm / °C or less.

[0030] The polyimide film may have a moisture absorption rate of 1.5 wt % or less.

[0031] On the other hand, the polyimide film of the present invention is prepared by dissolving 1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,19,20,21,22,23,24,18,19,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,52,6,7,8,9,10,25,32,33,34,35,36,37,38 ...42,52,6,7,8,9,10,25,32,33,34,35,36,37,42,52,6,7,8,9,10,25,32,33,34,35,36,37,42,52,6 Pan dianhydride, 2,3,3',4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride (BTDA), bis(3,4-dicarboxyphenyl)methane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, p-phenylene bis(trimeric monoester acid anhydride), p-biphenylene bis(trimeric monoester acid anhydride), m-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, p- one or more dianhydride acid components selected from the group consisting of terphenyl-3,4,3',4'-tetracarboxylic dianhydride, 1,3-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)biphenyl dianhydride, 2,2-bis[(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, and 4,4'-(2,2-hexafluoroisopropylidene)diphthalic dianhydride; Paraphenylenediamine (PPD), metaphenylenediamine, 3,3'-dimethylbenzidine, 2,2'-dimethylbenzidine, 2,4-diaminotoluene, 2,6-diaminotoluene, 3,5-diaminobenzoic acid (DABA), 4,4'-diaminodiphenyl ether (ODA), 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane (methylenediamine), 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 2,2'-bis(trifluoro methyl)-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dicarboxy-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, bis(4-aminophenyl)sulfide, 4,4'-diaminobenzanilide, 3,3'-dimethoxybenzidine, 2,2'-dimethoxybenzidine, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 3,3'-dia 3,4'-Diaminodiphenyl sulfide, 4,4'-Diaminodiphenyl sulfide, 3,3'-Diaminodiphenyl sulfone, 3,4'-Diaminodiphenyl sulfone, 4,4'-Diaminodiphenyl sulfone, 3,3'-Diaminobenzophenone, 4,4'-Diaminobenzophenone, 3,3'-Diamino-4,4'-dichlorobenzophenone, 3,3'-Diamino-4,4'-dimethoxybenzophenone, 3,3'-Diaminodiphenylmethane, 3,4'-Diaminodiphenylmethane, 4,4'-Diaminodi Phenylmethane, 2,2-bis(3-aminophenyl)propane, 2,2-bis(4-aminophenyl)propane, 2,2-bis(3-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 3,3'-diaminodiphenyl sulfoxide, 3,4'-diaminodiphenyl sulfoxide, 4,4'-diaminodiphenyl sulfoxide, 1,3-bis(3-aminophenyl)benzene, 1,3-bis(4-aminophenyl)benzene, 1,4-bis(3-aminophenyl)benzene, 1,4-bis(4-aminophenyl)benzene, 1,3-bis(4-aminophenoxy)benzene (TPE-R), 1,4-bis(3-aminophenoxy)benzene (TPE-Q), 1,3-bis(3-aminophenoxy)-4-trifluoromethylbenzene, 3,3'-diamino-4-(4-phenyl)phenoxybenzophenone, 3,3'-diamino-4,4'-di(4-phenylphenoxy)benzophenone, 1,3-bis(3-aminophenylsulfide)benzene, 1,3-bis(4-aminophenylsulfide)benzene, 1,4-bis(4-aminophenylsulfide)benzene, 1,3-bis(3-aminophenylsulfone)benzene, 1,3-bis(4-aminophenyl sulfone)benzene, 1,4-bis(4-aminophenylsulfone)benzene, 1,3-bis[2-(4-aminophenyl)isopropyl]benzene, 1,4-bis[2-(3-aminophenyl)isopropyl]benzene, 1,4-bis[2-(4-aminophenyl)isopropyl]benzene, 3,3'-bis(3-aminophenoxy)biphenyl, 3,3'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, bis[3-(3-aminophenoxy)phenyl]ether, bis[3-(4-aminophenoxy)phenyl]ether, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(4-aminophenoxy, )phenyl]ether, bis[3-(3-aminophenoxy)phenyl]ketone, bis[3-(4-aminophenoxy)phenyl]ketone, bis[4-(3-aminophenoxy)phenyl]ketone, bis[4-(4-aminophenoxy)phenyl]ketone, bis[3-(3-aminophenoxy)phenyl]sulfide, bis[3-(4-aminophenoxy)phenyl]sulfide, bis[4-(3-aminophenoxy)phenyl]sulfide, bis[4 -(4-aminophenoxy)phenyl]sulfide, bis[3-(3-aminophenoxy)phenyl]sulfone, bis[3-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[3-(3-aminophenoxy)phenyl]methane, bis[3-(4-aminophenoxy)phenyl]methane, bis[4-(3-aminophenoxy)phenyl] 2,2-bis[3-(3-aminophenoxy)phenyl]methane, bis[4-(4-aminophenoxy)phenyl]methane, 2,2-bis[3-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP), 2,2-bis[3-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hex The imidization reaction is carried out with one or more diamine components selected from the group consisting of 2,2-bis[3-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, and 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane.

[0032] The polyimide film is preferably obtained by an imidization reaction of a polyamic acid solution containing a dianhydride component including one or more selected from the group consisting of 3,3',4,4'-biphenyltetracarboxylic dianhydride (s-BPDA), pyromellitic dianhydride (PMDA), and 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), and a diamine component including one or more selected from the group consisting of paraphenylenediamine (PPD), 4,4'-diaminodiphenyl ether (ODA), and 2,2'-dimethylbenzidine.

[0033] In addition, based on 100 mol% of the total content of the dianhydride acid components, the content of the 3,3',4,4'-biphenyltetracarboxylic dianhydride may be 100 mol% or less, the content of the pyromellitic dianhydride may be 55 mol% or less, and the content of the 3,3',4,4'-benzophenonetetracarboxylic dianhydride may be 60 mol% or less.

[0034] On the other hand, based on 100 mol% of the total content of the diamine components, the content of the paraphenylenediamine may be 50 mol% or more and 100 mol% or less, the content of the 4,4'-diaminodiphenyl ether may be 20 mol% or less, and the content of the 2,2'-dimethylbenzidine may be 50 mol% or less.

[0035] If the content of pyromellitic dianhydride exceeds 55 mol %, the moisture absorption rate becomes very high, and the dimensional stability of the produced polyimide film against moisture may decrease. On the other hand, if the content of 3,3',4,4'-benzophenonetetracarboxylic dianhydride exceeds 60 mol %, the modulus of the produced polyimide film becomes too high and the film may become brittle.

[0036] In addition, if the content of paraphenylenediamine is less than 50 mol % or the content of 4,4'-diaminodiphenyl ether is more than 20 mol %, the thermal expansion coefficient of the produced polyimide film may become excessively high, resulting in reduced thermal dimensional stability. On the other hand, if the content of 2,2'-dimethylbenzidine exceeds 50 mol %, the modulus of the produced polyimide film becomes too high and the film may become brittle.

[0037] In the present invention, the polyamic acid can be produced, for example, by (1) A method in which the entire amount of the diamine component is placed in a solvent, and then the dianhydride component is added in an amount substantially equimolar to the diamine component to polymerize it; (2) A method in which the entire amount of the dianhydride component is placed in a solvent, and then a diamine component is added in an amount substantially equimolar to the dianhydride component to polymerize it; (3) A method in which a part of the diamine component is placed in a solvent, a part of the dianhydride component is mixed with the reaction components in a ratio of about 95 to 105 mol %, the remaining diamine component is added, and the remaining dianhydride component is added successively thereto, so that the diamine component and the dianhydride component are polymerized in substantially equimolar amounts; (4) A method in which a dianhydride component is placed in a solvent, a part of the components in the diamine compound is mixed in a ratio of 95 to 105 mol % relative to the reactive components, and then another dianhydride component is added, followed by the remaining diamine component, so that the diamine component and the dianhydride component are substantially equimolar, thereby polymerizing the mixture; (5) A method of forming a first composition by reacting some diamine components and some dianhydride acid components in a solvent so that one of them is in excess, and forming a second composition by reacting some diamine components and some dianhydride acid components in another solvent so that one of them is in excess, and then mixing the first and second compositions to complete polymerization, in which if the diamine component is in excess when the first composition is formed, the dianhydride acid component is in excess in the second composition, and if the dianhydride acid component is in excess in the first composition, the diamine component is in excess in the second composition, and the first and second compositions are mixed to polymerize so that the total diamine components and dianhydride acid components used in these reactions are substantially equimolar.

[0038] In one embodiment, a method for producing a polyimide film according to the present invention includes the steps of: providing a polyamic acid solution obtained from a dianhydride acid component and a diamine component; casting the polyamic acid solution onto a support and heating it to produce a self-supporting film of the polyamic acid solution; and imidizing the self-supporting film and stretching it to produce a polyimide film.

[0039] In the present invention, the polymerization method of the polyamic acid as described above can be defined as a random polymerization method, and a polyimide film prepared from the polyamic acid of the present invention prepared by the above process can be preferably applied in terms of maximizing the effect of the present invention of improving flatness.

[0040] However, in the above polymerization method, the length of the repeating unit in the polymer chain is relatively short, so that there may be a limit to the excellent properties of the polyimide chain derived from the dianhydride acid component. Therefore, the polymerization method of polyamic acid that can be preferably used in the present invention is a block polymerization method.

[0041] On the other hand, the solvent for synthesizing the polyamic acid is not particularly limited, and any solvent that dissolves the polyamic acid can be used, but an amide-based solvent is preferable. Specifically, the organic solvent may be an organic polar solvent, more specifically, an aprotic The solvent may be a polar solvent, for example, one or more selected from the group consisting of N,N-dimethylformamide (DMF), N,N-dimethylacetamide, N-methyl-pyrrolidone (NMP), gamma-butyrolactone (GBL), and diglyme, but is not limited thereto, and may be used alone or in combination of two or more kinds as needed. In one example, the organic solvent that can be particularly preferably used is N,N-dimethylformamide or N,N-dimethylacetamide.

[0042] In addition, in the process for producing the polyamic acid, a filler may be added for the purpose of improving various properties of the film such as sliding properties, thermal conductivity, corona resistance, loop hardness, etc. The filler to be added is not particularly limited, but preferred examples include silica, titanium oxide, alumina, silicon nitride, boron nitride, calcium hydrogen phosphate, calcium phosphate, mica, etc.

[0043] The particle size of the filler is not particularly limited and may be determined depending on the film properties to be modified and the type of filler to be added. In general, the average particle size is 0.05 to 100 μm, preferably 0.1 to 75 μm, more preferably 0.1 to 50 μm, and particularly preferably 0.1 to 25 μm. If the particle size is below this range, the modifying effect is unlikely to be achieved, whereas if it exceeds this range, the surface properties may be significantly damaged or the mechanical properties may be significantly reduced.

[0044] The amount of the filler to be added is not particularly limited, and may be determined depending on the film properties to be modified, the particle size of the filler, etc. In general, the amount of the filler to be added is 0.01 to 100 parts by weight, preferably 0.01 to 90 parts by weight, and more preferably 0.02 to 80 parts by weight, relative to 100 parts by weight of polyimide. If the amount of the filler added is less than this range, the modifying effect of the filler is unlikely to be exhibited, and if the amount exceeds this range, the mechanical properties of the film may be significantly damaged. The method of adding the filler is not particularly limited, and any known method may be used.

[0045] In the production method of the present invention, the polyimide film can be produced by a thermal imidization method or a chemical imidization method. Alternatively, the imidation layer may be produced by a hybrid imidation method in which a thermal imidization method and a chemical imidization method are performed in parallel.

[0046] The thermal imidization method is a method in which a chemical catalyst is excluded and the imidization reaction is induced by a heat source such as hot air or an infrared dryer.

[0047] The thermal imidization method can imidize the amic acid groups present in the gel film by heat-treating the gel film at a variable temperature in the range of 100 to 600°C, specifically, by heat-treating the gel film at 200 to 500°C, more specifically, by heat-treating the gel film at 300 to 500°C, to imidize the amic acid groups present in the gel film.

[0048] However, a portion of the amic acid (about 0.1 mol % to 10 mol %) may be imidized during the process of forming the gel film, and for this purpose, the polyamic acid composition may be dried at a variable temperature in the range of 50°C to 200°C, which may also be included in the category of the thermal imidization method.

[0049] In the case of the chemical imidization method, a polyimide film can be produced using a dehydrating agent and an imidization agent by methods known in the art.

[0050] As an example of the composite imidization method, a polyimide film can be produced by adding a dehydrating agent and an imidization agent to a polyamic acid solution, heating the solution at 80 to 200°C, preferably 100 to 180°C, partially curing and drying the solution, and then heating the solution at 200 to 400°C for 5 to 400 seconds. The present invention provides a flexible metal foil laminate comprising the above-mentioned polyimide film and an electrically conductive metal foil.

[0051] The metal foil used is not particularly limited, but when the flexible metal foil laminate of the present invention is used for electronic or electrical equipment applications, the metal foil may be, for example, copper or a copper alloy, stainless steel or its alloy, nickel or a nickel alloy (including alloy 42), aluminum or an aluminum alloy. In general flexible metal foil laminates, copper foils such as rolled copper foils and electrolytic copper foils are often used, and are also preferably usable in the present invention. In addition, the surface of these metal foils may be coated with an anti-rust layer, a heat-resistant layer, or an adhesive layer.

[0052] In the present invention, the thickness of the metal foil is not particularly limited, and may be any thickness that can exhibit sufficient functionality depending on the application.

[0053] The flexible metal foil laminate according to the present invention can be obtained by laminating, coating, sputtering or vapor-depositing a metal foil on at least one surface of the polyimide film. In addition, the flexible metal foil laminate can be used as a 2-layer FCCL, particularly for mobile phones, displays (LCD, PDP, OLED, etc.), and can be used for FPCB and COF.

[0054] The electronic component including the flexible metal foil laminate may be, for example, but is not limited to, a communication circuit for a mobile terminal, a communication circuit for a computer, or a communication circuit for an aerospace application. EXAMPLES

[0055] The functions and effects of the present invention will be described in more detail below through specific manufacturing examples and examples of the present invention, however, these manufacturing examples and examples are presented only as examples of the present invention and do not limit the scope of the invention.

[0056] Manufacturing example: Manufacturing of polyimide film The polyimide film of the present invention can be prepared by the following conventional method known in the art: First, the dianhydride and diamine components are reacted in an organic solvent to obtain a polyamic acid solution. The dianhydride and diamine components may be added in the form of powder, lump, or solution. It is preferable to add them in the form of powder at the beginning of the reaction to proceed with the reaction, and then add them in the form of a solution to adjust the polymerization viscosity. The resulting polyamic acid solution may be mixed with an imidization catalyst and a dehydrating agent and applied to a substrate.

[0057] Examples of the catalyst used include tertiary amines (e.g., isoquinoline, β-picoline, pyridine, etc.), and examples of the dehydrating agent include, but are not limited to, anhydrous acids. In addition, examples of the support used include, but are not limited to, glass plates, aluminum foils, circular stainless steel belts, stainless steel drums, etc.

[0058] The film coated on the support is gelled on the support by dry air and heat treatment. The gelled film is separated from the support and heat treated to complete drying and imidization. After the heat treatment, the film is heat treated under a certain tension to remove residual stress inside the film generated during the film formation process.

[0059] Specifically, 500ml of DMF was added to a reactor equipped with a stirrer and nitrogen inlet / outlet pipes while injecting nitrogen, and the temperature of the reactor was set to 30°C. Then, 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), pyromellitic dianhydride (PMDA), 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), paraphenylenediamine (PPD), 4,4'-diaminodiphenyl ether (ODA) and 2,2'-dimethylbenzidine (MTD) were added in the adjusted composition ratio and in the specified order and completely dissolved. After that, the temperature of the reactor was raised to 40°C under a nitrogen atmosphere and stirring was continued for 120 minutes to produce polyamic acid with a primary reaction viscosity of 1,500cP. The polyamic acid thus produced was stirred so as to have a final viscosity of 100,000 to 120,000 cP. The catalyst and dehydrating agent were added to the prepared final polyamic acid in an adjusted content, and then a polyimide film was produced using an applicator.

[0060] Examples and Comparative Examples Polyimide films were produced according to the above-mentioned Production Examples, except that the contents of dianhydride and diamine components in the Examples and Comparative Examples were adjusted as shown in Table 1 below.

[0061] [Table 1]

[0062] The dimensional measurement (200° C.), dimensional measurement (50° C.), coefficient of thermal expansion (CTE) and moisture absorption rate of the prepared polyimide film were measured and are shown in Table 2 below.

[0063] (1) Measurement of thermal expansion coefficient when heated The polyimide film was stored for 48 hours under a humidity condition of 50% RH, and then the dimensions of the polyimide film were measured by a thermomechanical analyzer (TMA) during the temperature rise process from 25°C to 400°C at 50°C and 200°C in the first run. The slope of a straight line connecting the measured dimension of the polyimide film and the measured dimension of the polyimide film at 50° C. in the first run during the temperature increase process was calculated. Typically, the coefficient of thermal expansion (CTE) is measured by measuring the slope (ppm / °C) of the temperature drop section of the first run and the temperature rise section of the second run in a thermomechanical analyzer (TMA) analysis. However, in order to measure the dimensional change of a polyimide film that is affected by the actual process and moisture, it is necessary to measure the slope (ppm / °C) of the temperature rise section of the first run in a thermomechanical analyzer (TMA) analysis, as in the present application.

[0064] (2) Measurement of thermal expansion coefficient The coefficient of thermal expansion (CTE) was measured using a TA thermomechanical analyzer. The polyimide film was cut to a width of 4 mm and a length of 20 mm, and the measurement length of the sample was 16 mm. At this time, the longitudinal direction of the sample measurement was the TD direction. Under a nitrogen atmosphere, the material was heated from room temperature to 400°C at a rate of 10°C / min while applying a tension of 0.05 N, and then cooled again at a rate of 10°C / min, while measuring the slope in the range from 50°C to 200°C. In other words, the thermal expansion coefficient corresponds to the slope measured during the cooling process after heating. Meanwhile, the thermal expansion coefficient corresponding to the slope measured during the temperature drop in the first run shows a similar value to the normal thermal expansion coefficient corresponding to the slope measured during the temperature rise in the second run.

[0065] (3) Moisture absorption rate measurement The moisture absorption rate was measured according to the ASTM D570 method by cutting a polyimide film into a square of 5 cm x 5 cm to prepare a test piece, drying the cut test piece in an oven at 50°C for 24 hours or more and measuring its weight, immersing the weighed test piece in water at 23°C for 24 hours and measuring its weight again, and expressing the weight difference as a percentage.

[0066] [Table 2]

[0067] The polyimide films of Examples 1 to 6 have a thermal expansion coefficient of -1.5 at 50 to 200°C. This corresponds to more than ppm / ℃ and less than 6 ppm / ℃. That is, as shown in the graphs of the dimensional change measurement results of the polyimide films of Examples 1 and 4 shown in FIGS. 1A and 1B, respectively, it was confirmed that the temperature-induced thermal expansion coefficient, which is the slope of the line connecting the measured dimensional value in the TD direction of the polyimide film measured at 200° C. during the temperature-raising process and the measured dimensional value in the TD direction of the polyimide film measured at 50° C. during the temperature-raising process, is in the range of −1.5 ppm / ° C. or more and 6 ppm / ° C. or less. On the other hand, in the graphs of the dimensional change measurements in FIGS. 1A and 1B, the dimensional change values ​​on the Y-axis indicate the dimensional change values ​​corresponding to the length (16 mm) of the polyimide film sample used in the TMA measurement. The thermal expansion coefficient at elevated temperature (50 to 200°C) was calculated from the slope obtained by converting the measurement results of the dimensional change measurement graph into a dimensional change value per meter of polyimide film length.

[0068] Moreover, the polyimide films of Examples 1 to 6 had a thermal expansion coefficient in the TD direction of 1 ppm / ° C. or more and 10 ppm / ° C. or less, and a moisture absorption rate of 1.5 wt % or less. In contrast, the polyimide films of Comparative Examples 1 and 4 had a pyromellitic dianhydride content exceeding 55 mol %, and the polyimide film of Comparative Example 5 had a paraphenylenediamine content less than 50 mol % and a 2,2'-dimethylbenzidine content exceeding 50 mol %. Therefore, the polyimide films of Comparative Examples 1, 4, and 5 had high moisture absorption rates or very low temperature-lowering thermal expansion coefficients, which caused shrinkage, and thus exhibited temperature-up thermal expansion coefficients (50 to 200°C) of less than -1.5 ppm / °C. That is, as shown in the graphs of the results of the dimensional change measurement of the polyimide films of Comparative Examples 1 and 4 shown in FIGS. 2A and 2B, respectively, the slope of the straight line connecting the dimensional measurement value in the TD direction of the polyimide film measured at 200° C. during the heating process and the dimensional measurement value in the TD direction of the polyimide film measured at 50° C. during the heating process, converted into a dimensional change value per meter of the polyimide film length, was less than −1.5 ppm / ° C.

[0069] On the other hand, the polyimide films of Comparative Examples 2 and 3 had a paraphenylenediamine content of less than 50 mol % and a 4,4'-diaminodiphenyl ether content of more than 20 mol %. As a result, the temperature-induced thermal expansion coefficient (50 to 200°C) became very large, exceeding the range of the temperature-induced thermal expansion coefficient (50 to 200°C) of the polyimide film of the present application, and the thermal expansion coefficient in the TD direction became very large, resulting in a decrease in the dimensional stability of the polyimide film.

[0070] The examples of the polyimide film and the method for manufacturing the polyimide film of the present invention are merely preferred examples that enable a person having ordinary skill in the art to easily carry out the present invention, and the present invention is not limited to the above-mentioned examples, and the scope of the present invention is not limited by these examples. Therefore, the true technical scope of the present invention must be determined by the technical ideas of the appended claims. In addition, it is obvious to a person skilled in the art that various substitutions, modifications and changes are possible within the scope of the present invention, and it is obvious that the parts that can be easily modified by a person skilled in the art are also included in the scope of the present invention. [Industrial Applicability]

[0071] The present invention provides a polyimide film that has excellent dimensional stability even after exposure to humidity for a certain period of time, and therefore provides a polyimide film that has excellent dimensional stability even during the lamination process of metal foil. Such polyimide films are applicable to various fields requiring polyimide films with excellent dimensional stability, for example, flexible metal foil laminates produced by a metallizing method or electronic parts including such flexible metal foil laminates.

Claims

1. After storing for 48 hours at 50% RH, In the measurement of dimensional change by a thermomechanical analyzer (TMA) during the temperature rise process from 25°C to 400°C, the temperature rise thermal expansion coefficient in the TD direction (50 to 200°C) is -1.5 ppm / °C or more and 6 ppm / °C or less, The temperature-rising thermal expansion coefficient (50 to 200° C.) is a slope of a line connecting a measured dimension of the polyimide film in the TD direction measured at 200° C. in the first run during the temperature-rising process and a measured dimension of the polyimide film in the TD direction measured at 50° C. in the first run during the temperature-rising process, The measured dimension in the TD direction corresponds to a dimensional change value calculated by converting the length of the polyimide film sample used in the measurement with the thermomechanical analyzer to 1 m. Polyimide film.

2. The thermal expansion coefficient in the TD direction is 1 ppm / °C or more and 10 ppm / °C or less. The polyimide film according to claim 1 .

3. The moisture absorption rate is 1.5 wt% or less. The polyimide film according to claim 1 .

4. Pyromeritic dianhydride (PMDA), oxydiphthalic dianhydride (ODPA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (s-BPDA), 2,3,3',4'-biphenyltetracarboxylic dianhydride (a-BPDA), diphenylsulfone-3,4,3',4'-tetracarboxylic dianhydride (DSDA), bis(3,4-dicarboxyphenyl)sulfide dianhydride, 2 , 2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 2,3,3',4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride (BTDA), bis(3,4-dicarboxyphenyl)methane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, p-phenylenebis(trimellite) monoester acid anhydride), p-biphenylene bis(trimeritic monoester acid anhydride), m-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, p-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, 1,3-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 1, one or more dianhydride acid components selected from the group consisting of 4-bis(3,4-dicarboxyphenoxy)biphenyl dianhydride, 2,2-bis[(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, and 4,4'-(2,2-hexafluoroisopropylidene)diphthalic dianhydride; Paraphenylenediamine (PPD), metaphenylenediamine, 3,3'-dimethylbenzidine, 2,2'-dimethylbenzidine, 2,4-diaminotoluene, 2,6-diaminotoluene, 3,5-diaminobenzoic acid (DABA), 4,4'-diaminodiphenyl ether (ODA), 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane (methylenediamine), 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dicarboxy-4,4'-diaminodiphenyl Methane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, bis(4-aminophenyl)sulfide, 4,4'-diaminobenzanilide, 3,3'-dimethoxybenzidine, 2,2'-dimethoxybenzidine, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 3 ,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminobenzophenone, 4,4'-diaminobenzophenone, 3,3'-diamino-4,4'-dichlorobenzophenone, 3,3'-diamino-4,4'-dimethoxybenzophenone, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 2,2-bis(3-aminophenyl)propane, 2,2-bis(4-aminophenyl)propane, 2,2-bis(3-aminophenyl)-1, 1,1,3,3,3-hexafluoropropane, 2,2-bis(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 3,3'-diaminodiphenyl sulfoxide, 3,4'-diaminodiphenyl sulfoxide, 4,4'-diaminodiphenyl sulfoxide, 1,3-bis(3-aminophenyl)benzene, 1,3-bis(4-aminophenyl)benzene, 1,4-bis(3-aminophenyl)benzene, 1,4-bis(4-aminophenyl)benzene, 1,3-bis(4-aminophenoxy)benzene (TPE-R) , 1,4-bis(3-aminophenoxy)benzene (TPE-Q), 1,3-bis(3-aminophenoxy)-4-trifluoromethylbenzene, 3,3'-diamino-4-(4-phenyl)phenoxybenzophenone, 3,3'-diamino-4,4'-di(4-phenylphenoxy)benzophenone, 1,3-bis(3-aminophenylsulfide)benzene, 1,3-bis(4-aminophenylsulfide)benzene, 1,4-bis(4-aminophenylsulfide)benzene, 1,3-bis(3-aminophenylsulfone)benzene, 1,3-bis(4-aminophenylsulfone)benzene, 1,4-bis(4-aminophenylsulfone)benzene, 1,3-bis[2-(4-aminophenyl)isopropyl]benzene, 1,4-bis[2-(3-aminophenyl)isopropyl]benzene, 1,4-bis[2-(4-aminophenyl)isopropyl]benzene, 3,3'-bis(3-aminophenoxy)biphenyl, 3,3'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, bis[3 -(3-aminophenoxy)phenyl]ether, bis[3-(4-aminophenoxy)phenyl]ether, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(4-aminophenoxy)phenyl]ether, bis[3-(3-aminophenoxy)phenyl]ketone, bis[3-(4-aminophenoxy)phenyl]ketone, bis[4-(3-aminophenoxy)phenyl]ketone, bis[4-(4-aminophenoxy)phenyl]ketone, bis[3-(3-aminophenoxy)phenyl]sulfide, bis[3-(4-aminophen bis[4-(3-aminophenoxy)phenyl]sulfide, bis[4-(4-aminophenoxy)phenyl]sulfide, bis[3-(3-aminophenoxy)phenyl]sulfone, bis[3-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[3-(3-aminophenoxy)phenyl]methane, bis[3-(4-aminophenoxy)phenyl]methane, bis[4-(3-aminophenoxy)phenyl 2,2-bis[3-(3-aminophenoxy)phenyl]methane, bis[4-(4-aminophenoxy)phenyl]methane, 2,2-bis[3-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP), 2,2-bis[3-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[3-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-Hexafluoropropane, 2,2-bis[4-, and one or more diamine components selected from the group consisting of 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane and 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane. The polyimide film according to claim 1 .

5. a dianhydride acid component including at least one selected from the group consisting of 3,3',4,4'-biphenyltetracarboxylic dianhydride (s-BPDA), pyromellitic dianhydride (PMDA) and 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA); and a diamine component including at least one selected from the group consisting of paraphenylenediamine (PPD), 4,4'-diaminodiphenyl ether (ODA) and 2,2'-dimethylbenzidine, The polyimide film according to claim 1 .

6. Based on 100 mol% of the total content of the dianhydride acid components, the content of the 3,3',4,4'-biphenyltetracarboxylic dianhydride is 100 mol% or less, the content of the pyromellitic dianhydride is 55 mol% or less, and the content of the 3,3',4,4'-benzophenonetetracarboxylic dianhydride is 60 mol% or less. The polyimide film according to claim 5 .

7. the content of the paraphenylenediamine is 50 mol % or more and 100 mol % or less, the content of the 4,4'-diaminodiphenyl ether is 20 mol % or less, and the content of the 2,2'-dimethylbenzidine is 50 mol % or less, based on 100 mol % of the total content of the diamine components; The polyimide film according to claim 5 .

8. A method for producing the polyimide film according to any one of claims 1 to 7, comprising the steps of: providing a polyamic acid solution obtained from a dianhydride acid component and a diamine component; casting the polyamic acid solution onto a support and heating it to produce a self-supporting film of the polyamic acid solution; and imidizing the self-supporting film and stretching it to produce a polyimide film. A method for producing a polyimide film.

9. A laminate comprising the polyimide film according to any one of claims 1 to 7 and an electrically conductive metal foil. Flexible metal foil laminate.

10. The metal foil is formed by coating, sputtering or vapor deposition.

10. The flexible metal foil laminate of claim 9.

11. The flexible metal foil laminate of claim 10. Electronic components.

Citation Information

Patent Citations

  • Polyimide film and its production

    JP1987236827A

  • Metallized polyimide film

    JP2007186586A

  • Method of producing polyimide film

    JP2010149494A

  • Method of manufacturing flexible electronic device

    JP2017126728A

  • Method for producing aromatic polyimide film wherein linear expansion coefficient in transverse direction is lower than linear expansion coefficient in machine direction

    US20110084419A1